2017
DOI: 10.1177/0886260517727495
|View full text |Cite
|
Sign up to set email alerts
|

Is Perceived Need for Action Among Women in Violent Relationships Nonlinear and, If So, Why?

Abstract: Despite the prevalence and impact of partner violence, we understand little about women's action taking except that it seems an unpredictable, nonlinear process. This article determines the degree of nonlinearity in perceived need for help, legal action, or leaving among women in violent relationships. The participants included 143 women who experienced violence in the previous month, enrolled from six primary care clinics. Baseline surveys assessed background characteristics and factors which may affect perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 78 publications
1
8
0
Order By: Relevance
“…However, prior analysis found that there were few malefemale reporting differences and that these daily reports were relatively complete (Burge et al, 2019). Even so, imputation of missing daily data generally has little effect on nonlinearity (Katerndahl et al, 2017). Finally, the predominance of low-income Hispanics within the sample may limit the generalizability of the findings.…”
Section: Limitationsmentioning
confidence: 88%
See 2 more Smart Citations
“…However, prior analysis found that there were few malefemale reporting differences and that these daily reports were relatively complete (Burge et al, 2019). Even so, imputation of missing daily data generally has little effect on nonlinearity (Katerndahl et al, 2017). Finally, the predominance of low-income Hispanics within the sample may limit the generalizability of the findings.…”
Section: Limitationsmentioning
confidence: 88%
“…When the initial data points in the time series were insufficient to apply nstep (generally n < 4), the mode of the time series was inserted until the time series is long enough to use nstep. To assess the effects of data imputation of nonlinearity assessment, we previously compared nonlinearity measures using all data sets (with and without imputed values) against those using only complete, nonimputed data sets and those with less than 25% of data imputed (Katerndahl et al, 2017). Although measures of both Lempel-Ziv (LZ) complexity (a measure of the amount of information needed to describe the data) and approximate entropy (ApEn; a measure of lack of regularity) increased with increasing use of imputed data, the incremental increases were small for both measures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On average, the most frequent and severe violence occurred with random dynamics (Katerndahl et al, 2014a). Measures of nonlinearity have consistently indicated that IPV varies nonlinearly (Katerndahl et al, 2014a(Katerndahl et al, , 2017a. How does the dynamics of the violence translate into the dynamics of decision-making?…”
mentioning
confidence: 99%
“…In fact, the degree of nonlinearity of each type of action seemed to be dependent upon a different source; while the nonlinearity of need-for-help was best explained by multiple, interdependent predictors and circular causality , the nonlinearity of need-for-legal-action was best understood via cusp catastrophe modeling (Katerndahl et al, 2017b). Nonlinearity of need-to-leave was best explained by its dependence upon the underlying nonlinear violence itself (Katerndahl et al, 2017a). Hence, partner violence and women's decisionmaking are complex, nonlinear phenomena embedded within a complex, nonlinear relationship.…”
mentioning
confidence: 99%